1978
DOI: 10.1029/ja083ia06p02543
|View full text |Cite
|
Sign up to set email alerts
|

Induced precipitation of inner zone electrons, 1. Observations

Abstract: Narrow precipitation spikes of energetic electrons observed in the inner zone drift loss cone during the 1968–1970 period by instrumentation on the OV1‐14 and OV1‐19 satellites are shown to have characteristics which are consistent with pitch angle scattering produced through a resonant interaction with ground‐based VLF transmissions. Analysis of the pitch angle distributions indicates that for virtually all of the events the electrons last interacted with the atmosphere in the vicinity of 55°–62° east longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 30 publications
(15 reference statements)
1
58
1
Order By: Relevance
“…Recent low-altitude satellite measurements of electrons in the drift loss cone between L -1.6 and L -1.8 display several characteristics which suggest that the electrons were precipitated by a resonant interaction with waves from a ground-based VLF transmitter [Vampola and Kuck, 1978;Imhof et al 1974a, b]. The easternmost edge of the pitch-angle scattering region can be determined from the size of the observed loss cone in the particle pitch-angle distribution under the following assumptions (1) the pitch-angle scattering is sufficiently strong to fill the drift loss cone to at least the edge of the local bounce loss cone, (2) the atmosphere removes all particles which have a mirror altitude below 100 km at the location where they have been pitch-angle scattered down from higher mirror altitudes and (3) that no further scattering occurs as the particles drift eastward.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent low-altitude satellite measurements of electrons in the drift loss cone between L -1.6 and L -1.8 display several characteristics which suggest that the electrons were precipitated by a resonant interaction with waves from a ground-based VLF transmitter [Vampola and Kuck, 1978;Imhof et al 1974a, b]. The easternmost edge of the pitch-angle scattering region can be determined from the size of the observed loss cone in the particle pitch-angle distribution under the following assumptions (1) the pitch-angle scattering is sufficiently strong to fill the drift loss cone to at least the edge of the local bounce loss cone, (2) the atmosphere removes all particles which have a mirror altitude below 100 km at the location where they have been pitch-angle scattered down from higher mirror altitudes and (3) that no further scattering occurs as the particles drift eastward.…”
Section: Introductionmentioning
confidence: 99%
“…The easternmost edge of the pitch-angle scattering region can be determined from the size of the observed loss cone in the particle pitch-angle distribution under the following assumptions (1) the pitch-angle scattering is sufficiently strong to fill the drift loss cone to at least the edge of the local bounce loss cone, (2) the atmosphere removes all particles which have a mirror altitude below 100 km at the location where they have been pitch-angle scattered down from higher mirror altitudes and (3) that no further scattering occurs as the particles drift eastward. Using the observed value of the loss-cone angle of electrons in the drift loss cone, Vampola and Kuck [1978] showed that the particles could be mapped westward in longitude to the region in which they were precipitated (see Vampola and Kuck [1978] for a discussion of this mapping procedure and the limits of accuracy). For precipitation events in the L range from 1.6 to 1.85, they found that most of the events mapped back to a small region of longitude near 600 E. Assuming a density model with a L -4 dependence and ducted propagation, Imhof et al r1974a, bi found that the particles they observed could resonate with ducted waves at a frequency of 10 kHz, which is very close to the lowest frequency used by the world-wide Omega navigation transmitters at 10.2 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…10 (VAMPOLA and KUCK, 1978). In this case the authors observe a pitch-angle distribution that is truncated well outside the local loss cone at east (geographic) longitudes >1000.…”
Section: Energetic-particle Loss Processesmentioning
confidence: 79%
“…sistent with equatorial cyclotron resonance with an unducted 16-kHz signal for reasonable plasma-density models (VAMPOLA and KUCK, 1978). It is tempting but dangerous to infer from such evidence that the radiation intensity in the magnetosphere was much higher in the years before those powerful VLF transmitters were installed around the world.…”
Section: Energetic-particle Loss Processesmentioning
confidence: 99%
See 1 more Smart Citation